Efficacy and safety of tranexamic acid in acute upper gastrointestinal bleeding: meta-analysis of randomised controlled trials. (1st December 2020) - Kamal, Faisal; Khan, Muhammad Ali; Lee-Smith, Wade; Sharma, Sachit; Imam, Zaid; Jowhar, Dawit; Petryna, Ellen; Marella, Hemnishil K.; Aksionav, Pavel; Iqbal, Umair; Tombazzi, Claudio; Howden, Colin W.
Abstract: Background: Studies evaluating the role of tranexamic acid in acute upper GI bleeding (UGIB) have reported conflicting results. In this systematic review, we have evaluated the efficacy and safety of tranexamic acid in UGIB. Methods: We searched several databases from inception to June 6, 2020 to identify randomised controlled trials (RCTs) that compared tranexamic acid and placebo in UGIB. Our outcomes of interest were mortality, rebleeding, all thromboembolic events, venous thromboembolic events, need for transfusion, endoscopic intervention and surgery. Pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using fixed effect model. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework to assess the certainty of evidence. Results: We included 12 RCTs comprising 14, 100 patients. We found no significant difference in mortality, pooled RR (95% CI) 0.87 (0.74–1.01), rebleeding, pooled RR (95% CI) 0.90 (0.79–1.02), need for surgery, pooled RR (95% CI) 0.86 (0.73–1.02), need for transfusion, pooled RR (95% CI) 1.00 (0.99–1.01) or thromboembolic events, RR (95% CI) 1.16 (0.87–1.56) between treatments. We found an increased risk of venous thromboembolic events with tranexamic acid, pooled RR (95% CI) 1.94 (1.23–3.05). Certainty of evidence based on the GRADE framework for the different outcomes ranged from low to very low. Conclusions: Tranexamic acid does not improve outcomes in UGIB and may increase the risk of venous thromboembolic events.